Pemanfaatan Aplikasi Microsoft Teams sebagai Media Pembelajaran Daring dalam Program Tahfidz Siswa Kelas 6 Sekolah Dasar Islam Terpadu Assaidiyah - Irennisa Aulia Firdaus; Dedih Surana (UNISBA Press, 2022)
Abstrack. This research is about how to use a digital application for learning tahfidzul Qur'an, as a result of the outbreak of the covid-19 virus and causing human activities around the world to turn completely digital and online. This includes the tahfidz class at an Islamic boarding school by utilizing the team's application Microsoft as an online learning tool. On this basis, this research focuses on